Social Policy in a Cold Climate : Policies and their Consequences since the Crisis - Vizard, Polly; Stewart, Kitty, 1970-; Hills, John, 1954-; Burchardt, Tania; Lupton, Ruth (Book collections on Project MUSE., 2016)
The financial crisis of 2008 led the United Kingdom's Labour Government to make changes - primarily cuts - to social programs and a wide range of social services. The subsequent Coalition Government followed those changes with much more dramatic cuts. This book offers the first in-depth empirical analysis of the two governments and their approach to social policy in a period of crisis, assessing policy aims, policy implementation, and measurable outcomes.